PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. BAKRIE SUMATERA PLANTATIONS - Wulandari Pratami; Hari Susanta Nugraha; Sendhang Nurseto (Universitas Diponegoro, 2015)
Human resources have a significant role in the organization activities. One of the importance of the management of human resources is to maintain the employee's performance. the organization have to pay much attention to the working environment and enact labor discipline around the employees that can influence their ability to carry out their duties and to make consistent performance of the employee.This study aims to determine the effect of labor discipline, the influence of the work environment, and the effect of both of labor discipline and the work environment towards employees performance at PT. Bakrie Sumatra Plantations. This study uses explanatory research methods which is research that seeks to explain and highlight the relationship between the variables proposed in the study and explain the influence of independent variables on the dependent variable, in addition to test the hypothesis. Research sample totaled 94 people taken using the slovin formula with probability sampling techniques. Then the data was analysed using validity, realiabilitas, regression, t and F tests. the results revealed that the majority of respondents stated that the labor discipline has a significant effect on employee performance as indicated by the t value of 47.170 > t table 1.984. whereas the work environment have significant impact to the performance of employees indicated by t value 8.378> t table 1.984. furthermore both of the labor discipline and the work environment have influence jointly on performance as indicated by F value of 1100.540 with significant value 0.000 <0.05. The biggest impact is contributed by working discipline that is equal to 98%. recommendation can be suggested that in terms of labor discipline the company should increase discipline the employee for example by applying a reducing salary for the late, provide regular training, and enact strict funishment to employees in order to bring deterent effect. For better work environment it is necessary to making more frequent cleaning activity. In regard to the ratio between the number of employees and the number of security personnel, the company should be able to rejuvenate for some working facilities. In regard of the employees performance the company's can provide some material and non-material motivation to spur employees to increase their work, to increase frequency of training and to increase quality control can be done to improve the quality of employment,and to gather employees in a gathering to further improve the relationship between the companies and employees.